Analysis of rice cultivation sustainability in rice production centre areas, Indonesia - Intan Salassa Dara; Dwi Prasetyo Gecci; Rizki Noor Syafira Syifani (BIO Web of Conferences)
Concerns about Indonesia's rice production have led to a focus on sustainable agriculture in agricultural policy. The expansion and development of sustainable rice farming land is still an urgent matter among stakeholders. This study aims to determine the sustainable rice cultivation index and factors that influence the sustainability of rice cultivation in Boyolali, Sragen, Klaten, Madiun, and Ngawi Regencies. The study was analyzed multidimensionally (5 dimensions: environment, economic, social, technology, and institution and policy) using the Multidimensional Scaling-RAPFISH method involving a total of 225 respondents. The results of the study showed that rice cultivation in Central Java and East Java was categorized as quite sustainable, with an average index of 59.85%. This means that, on average, farmers have carried out rice cultivation practices quite well. On average, the use of organic fertilizer, capital, OPT control, work safety instructions, and farmer participation in farmer groups are the factors that most influence sustainable rice cultivation. This study emphasizes the importance of sustainable rice cultivation practices, as well as the involvement of all stakeholders in increasing the capacity of farmer groups, extension workers, and business partners, as well as providing incentives, in the form of organic fertilizer subsidies, capital, and training.